1999
DOI: 10.1074/jbc.274.5.2696
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus DNA Replication

Abstract: Papovaviruses are valuable models for the study of DNA replication in higher eukaryotic organisms, as they depend on host factors for replication of their DNA. In this study we investigate the interactions between the human papillomavirus type 11 (HPV-11) origin recognition and initiator protein E1 and human polymerase ␣/primase (pol ␣/primase) subunits. By using a variety of physical assays, we show that both 180-(p180) and 70-kDa (p70) subunits of pol ␣/primase interact with HPV-11 E1. The interactions of E1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 62 publications
0
23
0
3
Order By: Relevance
“…Moreover, although Lys 425 is conserved among primate polyomavirus Tag proteins (45), it is not conserved among related viral helicases (e.g. papilloma virus E1 proteins), which also physically interact with and utilize pol-prim for viral DNA replication (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although Lys 425 is conserved among primate polyomavirus Tag proteins (45), it is not conserved among related viral helicases (e.g. papilloma virus E1 proteins), which also physically interact with and utilize pol-prim for viral DNA replication (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…For BPV, it has been demonstrated that ATP hydrolysis is required for displacement of E2 from the origin during assembly of E1 multimeric complexes (17). Either concurrent with or after formation of E1 oligomers, the host polymerase ␣ primase (21)(22)(23)(24)(25) and possibly also replication protein A (22,26) bind to E1, and a replication complex is formed together with additional host factors.…”
Section: From the Department Of Biological Sciences Boehringer Ingelmentioning
confidence: 99%
“…Since E2 affects ATP binding (K m ) rather than hydrolysis (k cat ), we would expect that ATP binding suffices to weaken the interaction of E1 with E2 (75), probably by inducing conformational changes in E1. In virus-infected cells, where E2 is present at low concentrations but ATP is in large excess, this perturbation of E2 binding could promote efficient viral DNA replication, since previous work by us (25) and others (23,24) has suggested that E2 must dissociate from E1 prior to association with the polymerase ␣ primase. Hence, saturation of E1 with ATP subsequent to E1 oligomerization may help release E1 from E2, and allow for its interaction with pol ␣ primase.…”
mentioning
confidence: 99%
“…E1 protein interacts directly with the p180 and p70 subunits of DNA polymerase ␣/primase (23)(24)(25)(26) and with RPA (27) and is required throughout the initiation and elongation stages, whereas E2 protein is needed only during initiation (28). E2 protein helps recruit E1 protein, preferentially from the homologous HPV genotype, to the origin (21,22,29).…”
mentioning
confidence: 99%